Machause, S., Rueda, C., Grau, I. y Roure, R. (eds.) (2021). Rock & Ritual. Caves, Rocky Places and Religious Practices in the Ancient Mediterranean. Collection “Mondes anciens”. Montpellier: Presses Universitaires de la Méditerranée-PULM. ISBN: 978-2-36781-424-7, 170 páginas. - Chapa Brunet, Teresa (SPAL - Revista de Prehistoria y Arqueología, 2023)
Recensión de la obra: Rock & Ritual. Caves, Rocky Places and Religious Practices in the Ancient Mediterranean